The impact of digital storytelling on psychosocial well-being in individuals with type 1 diabetes: a randomized clinical trial study in Iran - Sheyda Zamani; Samereh Abdoli; Fataneh Ghadirian; Leila Mardanian Dehkordi (BMC Psychology)
Abstract Background Living with diabetes presents psychosocial challenges, including distress, burnout, and depressive symptoms. Peer-created digital storytelling (DST) videos offer a platform for sharing personal experiences and management strategies, potentially improving psychological well-being and supporting better diabetes management. DST, grounded in Narrative and Social Cognitive Theory, provides an innovative, culturally adaptable, and low-cost intervention that addresses limitations of conventional psychosocial approaches. This study aimed to evaluate the effectiveness of DST in improving psychological outcomes in individuals with Type 1 Diabetes (T1D) in Iran. Methods This was a two-group, parallel, single-blind, randomized controlled trial (RCT) study conducted from July 2023 to May 2024. Sixty individuals with T1D were recruited from comprehensive health centers in Iran and randomly assigned in a 1:1 ratio to either the intervention group (n = 30) or the control group (n = 30) using MinimPy software. The intervention group participated in a 4-week program, where they viewed and discussed peer-created DST videos depicting successful T1D management, while the control group received routine care. Study outcomes, including diabetes distress, diabetes burnout, and depressive symptoms, were measured at baseline, immediately post-intervention, and one month post-intervention using validated scales. Data were analyzed using SPSS version 24.0, employing both descriptive and inferential statistics. Results The intervention group demonstrated significant improvement in mean scores for diabetes distress, diabetes burnout, and depressive symptoms at two time points (immediately post-intervention, and one-month post-intervention), with all p-values < 0.001. In contrast, no significant differences were observed in these scores at any time point within the control group (p > 0.05). Conclusion Reflecting on peer-created DST videos appears to be an effective intervention for reducing diabetes distress, diabetes burnout, and depressive symptoms in individuals with T1D. This study addresses a gap in the literature by evaluating a theory-driven, peer-led digital intervention in a low-resource setting. This approach could serve as a valuable model for mental health promotion initiatives in this population. Further research is needed to assess the long-term effects and sustainability of DST interventions. Trial registration This study was registered as a RCT at the Iranian Clinical Trial Center. Registration Date: 2023/07/05, Registration Number: IRCT20170625034743N2.